Contemporary Dynamics of Sharia Economic Law: DSN-MUI Fatwa No. 21/2001 in Takaful Dispute Rulings - Syihabudin; Rahmatullah; Najmudin; Henri Bimawan; Fandy Adpen Lazzavietamsi (Faculty of Sharia, IAIN Metro, 2025)
This research examines the role of Islamic law (Fatwa) in the formation and interpretation of positive law in Indonesia related to sharia insurance disputes, primarily through the decision of the Constitutional Court. Specifically, this study examines how the Supreme Court considers the DSN-MUI fatwa in resolving family takaful disputes, as well as how judicial authorities interpret, accept, or disregard the DSN-MUI fatwa as a consideration in such dispute cases within contemporary Sharia Economic law. Using normative juridical methods and jurisprudential analysis, this study analyses the decisions of the Constitutional Court that refer to Islamic principles such as justice (al-ʿadl), public interest (maṣlaḥah), and equality (musāwah). Data were obtained through the analysis of judicial decisions and Islamic law sources. The findings show that while Islamic law (specifically Fatwa) is not a formal source of national law, its values are selectively adopted in Constitutional Court decisions, especially in cases related to public morality, human rights, and Islamic finance. However, the integration of values is normative and symbolic but bare of methodological consistency based on uṣūl al-fiqh. This legal ambiguity limits the normative power of Islamic law and raises concerns about the protection of Muslim consumer rights. This study recommends institutionalizing Islamic legal reasoning through standardized methods of interpretation and increasing legal literacy among judges to promote consistent and substantial integration of sharia values in constitutional courts.